Development of a highly metastatic model that reveals a crucial role of fibronectin in lung cancer cell migration and invasion - Jia, Deshui; Yan, Mingxia; Wang, Xiaomin; Hao, Xiangfang; Liang, Linhui; Liu, Lei; Kong, Hanwei; He, Xianghuo; Li, Jinjun; Yao, Ming (BMC cancer, 2010)
The formation of metastasis is the most common cause of death in patients with lung cancer. A major implement to understand the molecular mechanisms involved in lung cancer metastasis has been the lack of suitable models to address it. In this study, we aimed at establishing a highly metastatic model of human lung cancer and characterizing its metastatic properties and underlying mechanisms. The human lung adeno-carcinoma SPC-A-1 cell line was used as parental cells for developing of highly metastatic cells by in vivo selection in NOD/SCID mice. After three rounds of selection, a new SPC-A-1sci cell line was established from pulmonary metastatic lesions. Subsequently, the metastatic properties of this cell line were analyzed, including optical imaging of in vivo metastasis, immunofluorescence and immunohistochemical analysis of several epithelial mesenchymal transition (EMT) makers and trans-well migration and invasion assays. Finally, the functional roles of fibronectin in the invasive and metastatic potentials of SPC-A-1sci cells were determined by shRNA analysis. A spontaneously pulmonary metastatic model of human lung adeno-carcinoma was established in NOD/SCID mice, from which a new lung cancer cell line, designated SPC-A-1sci, was isolated. Initially, the highly metastatic behavior of this cell line was validated by optical imaging in mice models. Further analyses showed that this cell line exhibit phenotypic and molecular alterations consistent with EMT. Compared with its parent cell line SPC-A-1, SPC-A-1sci was more aggressive in vitro, including increased potentials for cell spreading, migration and invasion. Importantly, fibronectin, a mesenchymal maker of EMT, was found to be highly expressed in SPC-A-1sci cells and down-regulation of it can decrease the in vitro and in vivo metastatic abilities of this cell line. We have successfully established a new human lung cancer cell line with highly metastatic potentials, which is subject to EMT and possibly mediated by increased fibronectin expression. This cell line and its reproducible s.c. mouse model can further be used to identify underlying mechanisms of lung cancer metastasis.